2018
DOI: 10.1055/s-0038-1673647
|View full text |Cite
|
Sign up to set email alerts
|

Right Potency Matters: A Case Report of Homoeopathic Treatment of Verruca Palmaris

Abstract: Warts are caused by human papilloma viruses (HPV) that can affect any part of the body including hands and feet. Verruca palmaris (VP) is a common manifestation due to HPV infection in keratinocytes of the palms. In the conventional system of medicine, VP is commonly managed through cauterisation, cryosurgery, surgical removal or topical ointments, which have many limitations. Scientific documentation for the treatment of VP by homoeopathic medicines is very scanty. In this context, the present case report is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Pediatric warts can be resolved within 2 years, but for an adult, it can stay for 5 to 10 years. 6,27 Some studies of successful treatment of warts are available in homoeopathic literature [12][13][14][15] but are not systematically documented through validated scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatric warts can be resolved within 2 years, but for an adult, it can stay for 5 to 10 years. 6,27 Some studies of successful treatment of warts are available in homoeopathic literature [12][13][14][15] but are not systematically documented through validated scales.…”
Section: Discussionmentioning
confidence: 99%
“…But after administration of the single homoeopathic medicine (Thuja occidentalis), the case displayed a speedy recovery (all warts were disappeared within 1 month and affected surfaces returned to the normal state within 3 months of disappearing warts without any external applications). Sahoo et al 15 suggested that the right potency is a crucial factor in bringing desired results. In this case, the potency (200CH) of the selected medicine (Thuja occidentalis) was a little higher, and thus slight aggravation of symptoms (itching on and around warts) was reported, but it was too short and subsequent rapid improvement took place within a plausible time frame.…”
Section: Spontaneous Remissionmentioning
confidence: 99%
See 1 more Smart Citation